Efektivitas Pelatihan Pengelolaan Laboratorium dan Workshop Pembelajaran Sains untuk SMP dengan Pendekatan Kearifan Lokal di Kepulauan Mentawai - Leony Sanga Lamsari Purba; Familia Novita Simanjuntak; Elferida Sormin; Nelius Harefa; Nova Irawati Simatupang; Sumiyati Sumiyati; St Fatimah Azzahra (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2022)
This community service activity is carried out to provide an understanding of environmental-based learning media, digital and virtual laboratories to teachers in the Mentawai Islands. The organizer of this PkM activity is the UKI Chemistry Education Study Program lecturer with Mentawai Islands teachers as participants. This activity starts from planning to evaluating the satisfaction of the implementation of PkM. Based on the information obtained, teachers who take part in the activities are generally teachers who teach <1 year (60%). Based on the evaluation results of the PkM service satisfaction survey, this activity was declared very feasible with a percentage of 92.8%. Furthermore, based on what was presented through a quiz to PkM participants, the most common activities regarding environment-based learning media and participants' expectations, in the future PkM writing papers will be held.